Effect of current density on porous silicon (pSi) for non-invasive dengue detection SERS substrates: electrical and structural property / N. F. Ismail ...[et al.] - Ismail, N.F.; Radzol, A.R.M.; Ismail, L.N.; Khuan, Y. Lee; Zulhanip, Aida Zulia; Mohamad Hadis, Nor Shahanim (UiTM Press, 2022)
Surface-Enhanced Raman Spectroscopy (SERS) is an ultra-sensitive and vibration-specific spectroscopy technique. It enhances Raman scattering by adsorbing molecules to roughen metal surfaces or colloidal nanoparticles known as SERS substrate. Enhancement performance of SERS is highly dependent on the type of substrate. This study sets out to examine the factors influencing the surface formation of porous Silicon (pSi) structure that is intended for SERS substrate for non-invasive Dengue detection at the febrile stage. The current density (J mA/cm2) in electrochemical etching process is one of such factors. Results of samples with different current density are documented in structural and electrical property. Field Emission Scanning Electron Microscopy (FESEM) images and surface structure of the SERS samples and cross-shapes porous structure are investigated. The current-voltage (I-V) property, conductivity versus resistivity property and sensitivity property of pSi structure are also examined. Results on structural property show that dimensions of the cross-shaped structures at different current density are visually almost the same. The averaged dimension ranges from 2.632 to 3.719 μm and depicts indeterminate trending with the current density. From the electrical property perspective, the I-V characteristic graphs of all samples show an exponentially rising trend, that bear similarity to the characteristic of diode. Besides, conductivity is found to increase with the current density. The ideal current density for producing porous structure is found to be that for the j-20 to j-28 samples, 20 to 28 mA/cm2.